ATM the broadband telecommunications solution - Cuthbert, L. G. (Laurie G.); Sapanel, J.-C. (Jean-Claude) (Institution of Electrical Engineers, 1993)
Since ATM was identified by the CCITT in 1988 as the target transfer mode for broadband communications, there has been considerable research activity on the topic world-wide. Within Europe, the RACE programme of the European Community has brought together experts from a wide variety of organisations to work on several projects. This book results from the work of one of those projects. Aimed at those interested in ATM generally, or those needing to understand the issues in designing or implementing broadband networks, the book draws on the results of the research project to present a description of ATM from a network point of view. Starting with the principles of ATM, it goes on to cover topics such as network performance, network structure, evolution and interworking. It also discusses more general issues including numbering, charging and the need for intelligence in the network. It concludes by explaining the current position on traffic engineering for broadband ATM networks.